Parenchymal-sparing hepatectomy for multiple bilobar colorectal liver metastases in a Jehovah’s witness: a case report - Shehan Ratnayake; Duminda Subasinghe; Vihara Dassanayake; Sivasuriya Sivaganesh (Journal of Liver Cancer, 2023)
Parenchymal-sparing hepatectomy (PSH), though technically challenging, is emerging as a choice of treatment for colorectal liver metastases (CRLM). PSH in Jehovah’s witness (JW) patients, for whom transfusion is not an option, involves complex surgical and medicolegal issues. A 52-year-old JW male with synchronous, multiple, bilobar liver metastases from a rectal adenocarcinoma was referred following neoadjuvant chemotherapy. At surgery, 10 metastatic deposits were observed and confirmed by intraoperative ultrasonography. Parenchymal-sparing non-anatomical resections were performed using a cavitron ultrasonic aspirator with the application of intermittent Pringle maneuvres. Histology confirmed multiple CRLMs with tumor-free resection margins. PSH is increasingly employed for CRLMs to preserve residual liver volume and minimize morbidity without compromising oncological outcomes. It is technically challenging, especially in the presence of bilobar, multi-segmental disease. This case illustrates the feasibility of performing complex hepatic surgery in special patient groups by meticulous planning and preparation involving multiple specialties and the patient.